2013
DOI: 10.1016/j.febslet.2013.07.024
|View full text |Cite
|
Sign up to set email alerts
|

The essential gene YMR134W from Saccharomyces cerevisiae is important for appropriate mitochondrial iron utilization and the ergosterol biosynthetic pathway

Abstract: a b s t r a c tA thermosensitive strain (YMR134W ts ) of the essential gene YMR134W presented up to 40% less ergosterol, threefold lower oxygen consumption and impaired growth on respiratory conditions. The iron content in the mitochondrial fraction of YMR134W ts cells was considerably low, despite these cells uptake and accumulate more iron from the culture media than wild-type cells. YMR134W ts cells were also more susceptible to oxidative stress. The results suggest that Ymr134wp is essential to aerobic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Defects in this step lead to the accumulation of toxic intermediates of the methyl sterol oxidase reaction that increase mitochondrial oxidation and affect the stability of the yeast frataxin homolog Ffh1, which is implicated in mitochondrial iron metabolism [13]. As a consequence, erg29 mutants exhibit defects in iron-sulfur cluster assembly and mitochondrial iron accumulation [13,115]. These results emphasize the multiple connections between iron metabolism and ergosterol biosynthesis.…”
Section: Regulation By Iron Bioavailabilitymentioning
confidence: 95%
See 1 more Smart Citation
“…Defects in this step lead to the accumulation of toxic intermediates of the methyl sterol oxidase reaction that increase mitochondrial oxidation and affect the stability of the yeast frataxin homolog Ffh1, which is implicated in mitochondrial iron metabolism [13]. As a consequence, erg29 mutants exhibit defects in iron-sulfur cluster assembly and mitochondrial iron accumulation [13,115]. These results emphasize the multiple connections between iron metabolism and ergosterol biosynthesis.…”
Section: Regulation By Iron Bioavailabilitymentioning
confidence: 95%
“…In any case, under iron deprivation, the loss of Dap1 is rescued by ERG11 overexpression but not by increasing heme biosynthesis [111]. In addition to Dap1, mutants in other components of ergosterol biosynthesis, such as in the essential genes ERG25 and ERG29, also lead to growth defects in low iron and respiratory conditions, respectively, due to impaired ergosterol production [114,115]. A recent study has revealed that, similarly to Erg25, Erg29 participates in the methyl sterol oxidase step of ergosterol biosynthesis [13].…”
Section: Regulation By Iron Bioavailabilitymentioning
confidence: 99%
“…The bm-8 mutant allele was a missense mutation in YMR134W, which encoded for a protein of unknown function. Moretti-Almeida et al (14) reported that a temperature-sensitive allele of YMR134W showed low mitochondrial iron accumulation at the restrictive temperature along with defects in ergosterol synthesis. Here, we report a detailed description of YMR134W, herein referred to as ERG29.…”
mentioning
confidence: 99%
“…A role for CTH2 in increasing resistance to ROS when this gene is overexpressed has been proposed (Matsuo et al, 2017). In case of YMR134W (ERG29), its function is related to ergosterol biosynthesis and has been tied to iron metabolism too (Moretti-Almeida et al, 2013). The common upregulation of YER037W (PHM8), which is involved in lysophosphatidic acid hydrolysis in response to phosphate starvation, suggests low availability of this nutrient too (Vardi et al, 2014).…”
Section: Transcriptional Response Of S Cerevisiae Cells To Differentmentioning
confidence: 99%